Calidad infantil, trabajo infantil, fertilidad y crecimiento económico - Yalonetzky, Gastón (2005)
In this paper I study the dynamic implications of household decisions that determine fertility and human capital accumulation with a theoretical model built on that of Hazan and Berdugo (2002). The links between the allocation of children's time, together with material resources towards child quality components, such as nutrition and the process of economic development are explored. I ive emphasis to investment in child quality because it has not previously been treated together with allocation of children's time in a dynamic setting. However these need to be dealt with together since they enable us explicitly to consider the possibility that human capital can be accumulated beyond the point at which child labor is effectively (rationally) eliminated, and even beyond that when fertility transition is concluded. I also show that this result can hold even in the absence of altruistic parents (in a unitary framework). Finally I show with these models that Caldwell's hypothesis about the correlation between intergenerational flows of resources and fertility regimes can be explained as being mediated by earning opportunities in educationally-intensive sectors which in turn influence parental incentives to invest in child quality.